An Investigation Of Switchable Matched Bandstop To Bandpass Filter Based On Lossy Resonator - Zahari, Mohd Khairy; Ahmad, Badrul Hisham; Wong , Peng Wen; Shairi, Noor Azwan; Mutalib, Mohamad Ariffin; Hassan, Nornikman (Penerbit Universiti, UTeM, 2017)
-